Fertility problems in males carrying an inversion of chromosome 10 - Zhang Xinyue (De Gruyter, 2021)
Chromosomal inversion is closely related to male infertility. Inversion carriers may produce abnormal gametes, which may lead to partial duplication/deletion of the embryonic chromosome and result in spontaneous abortion, a fetus with multiple anomalies, or birth of a malformed child. Genetic counselling remains challenging for these carriers in clinical practice. We report two male carriers with inversion of chromosome 10 and review 26 reported cases. In the first case, 46,XX,inv(10)(p13q22) of the fetal chromosome was found in prenatal diagnosis; this was inherited from the paternal side with 46XY,inv(10)(p13q22). Another case was a male carrier with inv(10)(q21.2q22.1). There have been 25 (89.3%) cases of pericentric inversion and three (10.7%) cases of paracentric inversion involving chromosome 10. Of 28 cases, nine were associated with pregestational infertility of the couples, while the other 19 cases were associated with gestational infertility of the couples or normozoospermia. The breakpoints at 10p15, 10p11, 10q11, and 10q21 were associated with pregestational infertility of the couples. The breakpoints at 10p15, 10p14, 10p13, 10p12, 10p11, 10q11, 10q21, 10q22, 10q23, 10q24, 10q25, and 10q26 were related to gestational infertility of the couples or normozoospermia. Although there is a high risk of infertility or recurrent miscarriages, carriers with inversion of chromosome 10 might produce healthy offspring. Natural pregnancy can be used as a choice for inversion carriers with recurrent spontaneous abortion.